Legal Reconstruction of Input Tax Credits That Have No Direct Relationship With Business Activities For Legal Certainty of Corporate Taxpayers - Setiawan, Wisnu Paruly; Ismail, Ismail; Setiawan, Puguh Aji Hari (jurnal.unprimdn.ac.id, 2026)
Taxes play a crucial role in national development, both as a source of state revenue and as an instrument for regulating the economy. Value Added Tax (VAT), with its Input Tax credit mechanism against Output Tax, is designed to maintain the principle of neutrality, but in practice it often raises legal issues. Article 9, paragraph 8, letter (b) of the VAT Law, concerning the phrase